Holistic view of intuition and analysis in leadership decision-making and problem-solving - Leonie Hallo; Nguyen Tiep (Administrative Sciences, 2022)
Making decisions is a key task for leaders and managers. Senior leaders are currently exposed to increasing amounts of data which they must process quickly in our current dynamic world. Complex factors in the business world are not always best approached through an analytical framework. Using tacit knowledge gained through intuition can enable a more holistic understanding of the deep nature of today's problems. This paper takes an expansive view of decision-making with intuition right at the centre and canvasses understandings of intuition arising from philosophy, psychology, Western and Eastern beliefs; and proposes a model that relates intuition to other problem-solving approaches. The paper presents the results of interviews with senior leaders who must make difficult decisions in complex turbulent environments. The interview schedule is based on questions raised in a prior literature search concerning the relationship between intuition and analysis in complexity decision-making and problem-solving, the usefulness to this group of respondents, the possibilities of combining both approaches and any conflict arising from that combination, and understandings of the concept of intuition by these respondents. The resultant model presents a visual description of a process that moves from exterior assessment achieved via sensing and analysis, through to deeper understandings and a more holistic discernment gained through intuition. The model has the potential to assist leaders faced with difficult-to-solve problems in providing a better understanding of the steps involved in tackling problems of increasing levels of complexity.
Keywords: 350; analysis; complexity; decision-making; intuition; leadership; problem-solving